Echocardiographic Screening of Rheumatic Heart Disease: Current Concepts and Challenges - Seda Topçu; Tayfun Uçar (AVES Yayincilik, 2024)
The incidence of acute rheumatic fever (ARF), which most commonly affects children aged 5-15 years after group A Streptococcus (GAS) infection, ranges from 8 to 51 per 100 000 people worldwide. Rheumatic heart disease (RHD), which occurs when patients with ARF are inappropriately treated or not given regular prophylaxis, is the most common cause of non-congenital heart disease in children and young adults in low-income countries. Timely treatment of GAS infection can prevent ARF, and penicillin prophylaxis can prevent recurrence of ARF. Secondary prophylaxis with benzathine penicillin G has been shown to decrease the incidence of RHD and is a key aspect of RHD control. The most important factor determining the prognosis of RHD is the severity of cardiac involvement. Although approximately 70% of patients with carditis in the acute phase of the disease recover without sequelae, carditis is important because it is the only complication of ARF that causes sequelae. One-third of patients with ARF are asymptomatic. Patients with mild symptoms of recurrent ARF and silent RHD will develop severe morbidities within 5-10 years if they do not receive secondary preventive treatments. A new screening program should be established to prevent cardiac morbidities of ARF in moderate- and highrisk populations. In the present study, we examined the applicability of echocardiographic screening programs for RHD.